Seeking researchers, limiting research: Renacyt and its contradictions - Bermúdez-Tapia, Manuel (2024)
As of October 2023, Renacyt reports a total of 97 "researcher" lawyers out of a national total of 6860. The system that records and weighs scientific research activity is applied to lawyers without taking into account the specific characteristics of the profession. It is assumed that similar evaluation methods could be applied to professionals such as doctors, biologists, or engineers without a clear differentiation of professional objectives. Given this situation, we question the Renacyt regulations in order to propose effective and valid solutions for all professional fields. While "research" is demanded, the method for validating these activities promotes situations that are unrelated to ethical considerations, professionalism, and any framework for research development.